Imaging the Source Region of the 2015 Phreatic Eruption at Owakudani, Hakone Volcano, Japan, Using High‐Density Audio‐Frequency Magnetotellurics. Issue 1 (13th January 2021) - Seki, K.; Kanda, W.; Mannen, K.; Takakura, S.; Koyama, T.; Noguchi, R.; Yukutake, Y.; Ishikawa, M.; Fukai, M.; Harada, M.; Abe, Y.
Abstract: Since phreatic eruptions often occur near the surface, it is important to understand the shallow subsurface structure of a volcano to clarify the eruption mechanism. The 2015 phreatic eruption at Owakudani, Hakone Volcano, Japan, was preceded by localized uplift and intensified steam activity. However, the cause of these events is unknown due to a poor understanding of the shallow subsurface structure. We report on a three‐dimensional resistivity structure inferred from dense audio‐frequency magnetotelluric surveys conducted in Owakudani that revealed a ∼100‐m thick conductive layer at the surface underlain by a resistive section, at the edge of which eruptions craters were located. This conductive layer is estimated to be a low‐permeability cap layer, because the inflation source prior to the eruption is located beneath it and the ejecta from the eruption was reported to have originated from a depth of 100 m or less. Plain Language Summary: Phreatic eruptions occur as a result of the rapid expansion of water that is heated by a source such as magma. Ejecta from these eruptions does not contain magmatic material, but often contains hydrothermally altered rocks. Understanding the hydrothermal system that develops in shallow volcanic structures is important to understand how phreatic eruptions occur. We imaged the subsurface structure of Owakudani, Hakone Volcano, Japan, where small phreatic eruptions took place in 2015. We found that an ∼100‐m thick layer near the surface is a key structure that may have caused the phreatic eruption. Formation of this characteristic structure is useful for evaluating the potential for phreatic eruptions elsewhere. Key Points: We estimated the 3‐D resistivity structure of Owakudani, Hakone Volcano, where phreatic eruptions occurred in 2015 A ∼100‐m thick conductive layer near the surface of Owakudani played an important role in causing the phreatic eruptions